2016
DOI: 10.1098/rstb.2015.0162
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of fire and mankind: Introduction

Abstract: One contribution of 24 to a discussion meeting issue 'The interaction of fire and mankind'. Fire has been an important part of the Earth system for over 350 Myr. Humans evolved in this fiery world and are the only animals to have used and controlled fire. The interaction of mankind with fire is a complex one, with both positive and negative aspects. Humans have long used fire for heating, cooking, landscape management and agriculture, as well as for pyrotechnologies and in industrial processes over more recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…Like many Quaternary deposits, the fluvial sequence in Arlington Canyon contains a significant quantity and range of organic material, much of which has been charred. Abundant charcoal implies the occurrence of fire, but whether these fires were started by lightning, humans or extraterrestrial impact requires additional lines of evidence (Hardiman et al , ; Scott et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Like many Quaternary deposits, the fluvial sequence in Arlington Canyon contains a significant quantity and range of organic material, much of which has been charred. Abundant charcoal implies the occurrence of fire, but whether these fires were started by lightning, humans or extraterrestrial impact requires additional lines of evidence (Hardiman et al , ; Scott et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies of palaeo-wildfires are related to the wildfires occurred in the Late Paleozoic era (Arzadún et al, 2017;Jasper et al, 2013;Kauffmann et al, 2016;Manfroi et al, 2015;Shen et al, 2011;Singh and Shukla, 2004;Sun et al, 2017). These palaeo-wildfires consumed O 2 and released CO, CO 2 to the atmosphere which modified the atmospheric temperatures and ecosystems (Berner, 2006;Lenton, 2013;Scott and Glasspool, 2006;Scott et al, 2016). Sun et al (2017) have reported also that the palaeowildfires of the Middle Permian could have discharged massive quantities of pollutants and increased the ambient temperature, causing the floral extinction that occurred at the Middle Permian.…”
Section: Wildfire Evidence From the Middle And Late Permian Hanxingmentioning
confidence: 99%
“…Wildfire is a natural phenomenon since Ordovician-Silurian period when plants were introduced to the ecosystem. However, occurrences of wildfires are increasing in present days due to anthropogenic causes and the interrelationships between the wildfire and the future of mankind are coming into more light (Scott et al, 2016). Palaeo-wildfires are an important factor in the evolution of past climates, and therefore their study is relevant for the prediction of climate changes on earth (Flannigan et al, 2009;Freeman and Cattell, 1990;Grasby et al, 2011;Lenton, 2013;Scott and Glasspool, 2006;Shen et al, 2011;Sun et al, 2017;Yan et al, 2019;Xu et al, 2020a,…”
Section: Introductionmentioning
confidence: 99%
“…It is today recognized that humans have influenced and shaped fire regimes, i.e., the set of biophysical parameters characterizing the pattern of fire occurrence in time and space (Krebs et al 2010;Pyke et al 2010), on every inhabited continent for millennia (Bowman et al 2011;Scott et al 2016). The nineteenth century marked radical shifts in the Earth's fire regimes, linked with rapid socioeconomic changes, notably in the "Western" world where industrialization induced the development of modern forestry.…”
Section: Introductionmentioning
confidence: 99%
“…Fire thus came to be seen as a threat for silvicultural resources, and fire suppression was widely applied in the forests of the USA, Europe, and its colonies. In some regions, the counterpart of fire suppression was the buildup of fuel loads in forests, leading to catastrophic wildfires (Pyne 1997;Pausas and Keeley 2009;Krebs et al 2010;Bowman et al 2011;Scott et al 2016). From the 1960s, fire has been increasingly recognized as a natural disturbance essential for the functioning of many ecosystems and for maintaining biodiversity (Shlisky et al 2007;Kuuluvainen et al 2002;Pausas and Keeley 2009;Krebs et al 2010).…”
Section: Introductionmentioning
confidence: 99%